PERAN MAHASISWA KKN DALAM PENGEMBANGAN EKONOMI KREATIF BERBASIS KOMUNITAS DI LAPAS BINAAN II-B KOTA PADANGSIDIMPUAN - Nur Sahara; Nurmaini Ginting; Fatma Suryani; Melvarianisyari; Khairul Nasution; Davina Davarisa; Khairun Nisa Dalimunthe; Afifah Luthfiyah (Smart Education, 2026)
This study aims to analyze the role of Community Service Program (KKN) students in developing a community-based creative economy at the Class II-B Penitentiary in Padangsidimpuan City. The background of this study is based on the importance of empowering inmates through productive activities that can improve skills, independence, and economic opportunities after the correctional period. The research method used was a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included KKN students, prison officers, and inmates involved in the creative economy program. The results showed that KKN students acted as facilitators, motivators, and mentors in developing creative economy activities, such as handicraft training, simple product processing, and digital-based marketing. The program implemented was able to improve the technical skills and self-confidence of inmates, although there were still obstacles such as limited facilities, market access, and program sustainability. Therefore, synergy is needed between the prison, universities, and relevant stakeholders to support the development of a sustainable creative economy.